(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study was conducted to assess utilization of preventive healthcare services among academic staff in University of Maiduguri, Borno State, Nigeria. Two hypotheses guided the study. Descriptive survey research design was used for the study; simple random sampling technique was also used for the study. A sample of 200 academic staff was drawn from seven faculties in the university. Data were collected using self-structured questionnaire with two sections, demographic data and utilization of preventive healthcare services. Data were analyzed using descriptive statistics of frequency counts and percentage while inferential statistics of one sample t-test and independent t- test was used to test hypotheses at 0.05 significance level. The result showed among others that there is significance difference in utilization preventive healthcare services and there is significant difference in gender utilization of preventive healthcare services. It was recommended among others that periodic public campaigns should be organized by the department of Physical and Health Education on the need for preventive measures to prevent preventable diseases.